Endocytic Pathways and Recycling in Growing Pollen Tubes - Onelli, Elisabetta (Plants (Basel), 2013)
Pollen tube growth is based on transport of secretory vesicles into the apical region where they fuse with a small area of the plasma membrane. The amount of secretion greatly exceeds the quantity of membrane required for growth. Mechanisms of membrane retrieval have recently been demonstrated and partially characterized using FM (Fei Mao) dyes or charged nanogold. Both these probes reveal that clathrin-dependent and -independent endocytosis occur in pollen tubes and are involved in distinct degradation pathways and membrane recycling. Exocytosis, internalization and sorting of PM proteins/lipids depend on the integrity of the actin cytoskeleton and are involved in actin filament organization. However, some kinds of endocytic and exocytic processes occurring in the central area of the tip still need to be characterized. Analysis of secretion dynamics and data derived from endocytosis highlight the complexity of events occurring in the tip region and suggest a new model of pollen tube growth.